Meteorology today an introduction to weather, climate, and the environment - Ahrens, C. Donald; Henson, Robert (Brooks/Cole, Cengage Learning, 2021)
Written by meteorologists C. Donald Ahrens and Robert Henson and grounded in the scientific method, METEOROLOGY TODAY: AN INTRODUCTION TO WEATHER, CLIMATE, AND THE ENVIRONMENT, 13th edition, shows you how to observe, calculate and synthesize weather information as a scientist. Packed with engaging visuals, it provides the latest information on climate change, ozone depletion, air quality, El NiÃ±o and other key topics as well as discussions of recent high-profile weather events, including droughts, heat waves, tornado outbreaks and hurricanes. "Focus On" boxes help you delve deeper into meteorological observation methods and environmental issues, while case studies provide direct access to academic and newsworthy papers on recent developments. The MindTap for Meteorology digital platform includes concept check activities, animations and videos, and a variety of hands-on activities.
Don Ahrens is professor emeritus at Modesto Junior College in Modesto, California. He has influenced countless professionals in the field of atmospheric science, as well as hundreds of thousands of students who use his books to better understand weather and climate.
Keywords: Meteorology -- Textbooks; Meteorologie; Einführung